FAULT PATTERN AND ACTIVE DEFORMATION OF OUTER ARC RIDGE OF NORTHWEST OF SIMEULUE ISLAND, ACEH, INDONESIA - Haryadi Permana; K. Hirata (BULLETIN OF THE MARINE GEOLOGY, 2011)
New bathymetric map of northwest Simeuleu Island area (3° 01’N-4°57’N and 93°16’E-94°08’E) has evidently illustrated fine morphological image of Outer Arc ridge and Aceh Fore Arc. The structural lineament pattern, inferred from the bathymetric map, could define in general elongated major NW-SE thrust fault complex, thrust fold, or bedding trace and N-S, NNE-SSW, WNW-ESE or ENE-WSW and E-W structural lineament trend. High intensity deformation processes related to high degree obliquity subducted plate was represented by rough and sigmoidal morphological shape, landward and steep to very steep dip angle of bedding plan. Rough morphology, V to U shape valley, dissected ridge and circular shape of landslide trace are common morphology features of active deformation zone. In the near future, high resolution marine seismic will be planned across this area to capture and confirm the subsurface structure configuration and fault movement. Keyword: bathymetric map, Outer Arc ridge, thrust fault, thrust fold, bedding trace, sigmoidal morphological, V to U shape valley,and landslide. Peta batimetri baru di sebelah barat laut Pulau Simelue (3° 01’LU - 4°57’LU and 93°16’BT-94°08’BT), memperlihatkan citra morfologi yang halus pada punggungan busur luar dan busur depan Aceh. Pola kelurusan struktur mengacu pada peta batimetri, dibagi dalam komplek sesar naik yang berarah umum baratlaut - tenggara, lipatan, atau jejak perlapisan dengan kecendrungan arah struktur utara-selatan, utara timur laut – selatan barat daya, barat - barat daya, timur tenggara atau timur laut - barat daya dan timur - barat. Proses deformasi intensitas tinggi berkaitan dengan derajat kemiringan penunjaman yang tinggi, diwakili oleh bentuk morfologi sigmoid dan kasar, ke arah darat dicirikan oleh kemiringan bidang lapisan terjal hingga sangat terjal. Bentuk morfologi kasar seperti bentuk lembah V hingga U, punggungan yang terpotong dan bentuk melingkar dari jejak longsoran merupakan gambaran morfologi umum dari zona deformasi aktif. Dalam waktu dekat, seismik laut resolusi tinggi akan direncanakan memotong daerah ini untuk menggambarkan dan mengkonfirmasi konfigurasi struktur bawah permukaan dan pergerakan sesar. Kata kunci : peta batimetri, punggungan busur luar, sesar naik, lipatan, jejak bidang perlapisan, morfologi sigmoid, bentuk lembah V hingga U,dan longsoran.